2016
DOI: 10.1111/acer.12964
|View full text |Cite
|
Sign up to set email alerts
|

Association of Drinking Problems and Duration of Alcohol Use to Inhibitory Control in Nondependent Young Adult Social Drinkers

Abstract: Background Deficits in inhibitory control have been widely implicated in alcohol misuse. However, the literature does not readily distinguish the effects of drinking problems and chronic alcohol use. Here, we examined how years of drinking and the Alcohol Use Disorders Identification Test (AUDIT) score each influences the cerebral responses to inhibitory control in non-dependent drinkers. Methods Fifty-seven adult drinkers and 57 age and gender matched non-drinkers participated in one 40-minute fMRI scan of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 54 publications
0
15
2
Order By: Relevance
“…In our previous fMRI study of social drinkers, higher AUDIT score was correlated with impaired inhibition and diminished responses in the cerebellum, thalamus, frontal and parietal regions, independent of years of alcohol use (Hu et al, 2016). Many other studies specifically support a role of the thalamus in impulsivity related symptomatology in neuropsychiatric illnesses including ADHD and addiction (Bailey and Joyce, 2015, Fassbender et al, 2015, Hu et al, 2015, Hu et al, 2016, Joseph et al, 2015, Kose et al, 2015, Li et al, 2010, Zhang et al, 2016). In particular, changes in thalamic GMVs have been noted in various clinical conditions that implicate impulsivity.…”
Section: Discussionmentioning
confidence: 93%
“…In our previous fMRI study of social drinkers, higher AUDIT score was correlated with impaired inhibition and diminished responses in the cerebellum, thalamus, frontal and parietal regions, independent of years of alcohol use (Hu et al, 2016). Many other studies specifically support a role of the thalamus in impulsivity related symptomatology in neuropsychiatric illnesses including ADHD and addiction (Bailey and Joyce, 2015, Fassbender et al, 2015, Hu et al, 2015, Hu et al, 2016, Joseph et al, 2015, Kose et al, 2015, Li et al, 2010, Zhang et al, 2016). In particular, changes in thalamic GMVs have been noted in various clinical conditions that implicate impulsivity.…”
Section: Discussionmentioning
confidence: 93%
“…These measures are predictive of clinical outcomes such as the duration of abstinence after treatment [ 30 ]. Results of functional magnetic resonance imaging (fMRI) studies using executive tasks are less consistent with some studies showing decreased [ 31 , 32 , 33 ], and others reporting increased activation in participants with AUD compared with controls [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Activation increase in AUD participants is commonly observed in the absence of executive task performance deficits suggesting that compensatory mechanisms are engaged to maintain normative behavioral performance especially on tasks imposing higher cognitive demands.…”
Section: Introductionmentioning
confidence: 91%
“…We contrasted successful stop and go trials, in that this contrast captures the saliency process evoked by the stop signal that is necessary to elicit the inhibitory process (Cai et al, 2016;Duann et al, 2009;Hu, Zhang, Chao, Krystal, & Li, 2016). Two SST studies reported age-related increases in activations in the motor and frontal regions when inhibitory control was examined by contrasting successful and unsuccessful stop trials (Bloemendaal et al, 2016;Kleerekooper et al, 2016).…”
Section: Age-related Decrease In Activation To Inhibitory Controlmentioning
confidence: 99%